Occupational Safety, Health, and Environmental (HSE/K3L) Risk Assessment of Ship Agency Personnel During Vessel Clearance Operations at PT Pelindo Marine Service - Ahmad Muzakky; Nisha Desfi Arianti; Tri Mardalena (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose of the study: This research aims to comprehensively evaluate K3L risks encountered by ship agency officers at PT Pelindo Marine Service during the ship clearance process and to assess the effectiveness of existing risk control measures. Materials and methods: A qualitative descriptive case study approach was employed, utilizing the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. Data were collected through direct field observations, in-depth interviews with 10 respondents (ship agency officers, operational supervisors, and HSE officers), structured questionnaires, and analysis of company documents. Risk assessment was conducted using a Risk Assessment Matrix considering likelihood, severity, and risk rating parameters. Data analysis followed the Miles and Huberman model involving data reduction, data presentation, and conclusion drawing. Results: The study identified five main activity categories with varying risk levels. The highest risk was found in boarding and disembarking activities via pilot ladder (high risk: moderate probability × severe impact), particularly during adverse weather and nighttime operations. Moderate risks were identified for exposure to engine exhaust fumes, work fatigue, and stress from inter-agency coordination. While PT Pelindo Marine Service has implemented various control measures including mandatory Personal Protective Equipment (PPE), toolbox meetings, periodic K3L training, and direct supervision, gaps in individual compliance and limited oversight during peak operational hours remain significant challenges. Conclusions: The HIRARC-based evaluation revealed that although existing control measures are partially effective, systematic improvements are necessary, particularly for high-risk activities. Strengthening safety protocols, enhancing staff compliance monitoring, implementing digital safety technologies, and fostering a robust safety culture are essential for minimizing occupational accidents and ensuring sustainable maritime operations.